Maxillofacial education in the time of COVID-19: the West Midlands experience. Issue 1 (January 2022) - Elledge, R.; Williams, R.; Fowell, C.; Green, J.
Abstract: COVID-19 has accelerated a reliance on virtual technology for the delivery of postgraduate surgical education. We sought to develop a regional teaching programme with robust quality assurance. Webinars were delivered on a weekly basis by subspecialty experts using Zoom™ augmented with interactive polling software. Trainee feedback comprised Likert item rating on content and delivery, free text comments and self-assessed confidence levels using visual analogue scale (VAS) scores. A focus group was also convened and transcripts assessed with grounded theory analysis. Likert items revealed 442 (93.2%) positive responses regarding content and 642 (96.7%) positive responses regarding trainer delivery. There were statistically significant improvements in VAS scores across all programme content. Key themes from the focus group analysis were the pragmatics of delivering online education, issues surrounding trainer interactivity in the virtual world, the identification of the FRCS as a driving factor and a desire for case-based content and pre-learning of information (the 'flipped classroom'). We are continuing to be reactive to trainee feedback in developing our online learning programme which will also include a regional Moodle-based virtual learning environment (VLE), the subject of future educational research in our region.